Autonomous Multifunctional Vehicle With Integrated Bio-Inspired SMA Actuated Grasper - Changoski, Vasko; Domazetovska, Simona; Anachkova, Maja; Jovanova, Jovana (American Society of Mechanical Engineers, 2020)
Abstract The space exploration activities are merging new technologies in order to develop systems challenged to achieve capabilities for high mission experience. Inspired by the numerous applications in space exploration, with the integration of shape memory alloys (SMAs), a 3D printed continuous All Terrain Grasper Transport (AT-GT) vehicle with implemented multi-locomotion grasper was created. In order to reduce failure of the mechanical system, the vehicle is equipped with SMA suspension and SMA tensioner of a pulley system with adaptable height able to achieve movement on a given trajectory and adjust to any terrain. SMA actuators provide controllable actuation based on the simplicity of their design and the shape memory effect. By using the advantages of the origami engineering, soft robotics and smart material implementation, a bio-inspired autonomous grasper was integrated on the AT-GT, capable of leaving the vehicle, grabbing an object and bringing it back to the vehicle. The concept development, the analytical models and the prototype including the benefits of the combined work of the vehicle and the grasper are presented.